Overview of irrigation policy in tanzania objectives and key questions j makoi - Makoi, Joachim H. J. R. (2016)
Presented by Dr. Joachim H.J.R. Makoi, National Irrigation Commission, Ministry of Water and Irrigation/ National Irrigation Commission Representative, at the workshop on “New Directions for Irrigation Development in Tanzania: The Context of Public Private Partnership”, September 2, 2016. https://www.ifpri.org/event/new-directions-irrigation-development-tanzania